PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SUBTEMA 1 KEKAYAAN SUMBER ENERGI DI INDONESIA - Amalia Septian Pandani; Tustiyana Windiyani; Mira Mirawati; Dadang Kurnia (Universitas Pakuan, 2021)
THE EFFECT OF THE APPLICATION OF THE DISCOVERY LEARNING OUTCOMES OF SUB-THEME 1 OF THE WEALTH OF ENERGY SOURCES IN INDONESIAThe Effect of “Application Influence Discovery Learning Model on Learning Outcomes Subtheme 1 Wealth Energy Sources in Indonesia